Persepsi Penumpang terhadap Kinerja Pengemudi Ojek Online: Studi Kualitatif pada Platform Transportasi Digital - Rijatul Anwar (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2026)
The rapid growth of app-based motorcycle taxi services has transformed urban mobility in Indonesian cities, including South Tangerang, while simultaneously raising concerns about service quality, safety, and the fairness of performance evaluation systems. This study aims to explore passengers’ perceptions of online motorcycle taxi drivers’ performance using a qualitative phenomenological approach. A total of 30 active users were selected through purposive sampling, focusing on passengers who regularly use ride-hailing services and have experience providing ratings or reviews. Data were collected through in-depth interviews, non-participatory observations, and documentation of user reviews. The analysis followed Miles, Huberman, and Saldaña’s interactive model, encompassing data reduction, data display, and conclusion drawing. The findings reveal five key themes shaping passengers’ perceptions: riding safety, driver responsiveness, communication and service etiquette, cleanliness and professional appearance, and perceived fairness of the rating algorithm. A statistical simulation based on respondents’ rating distributions produced an average score of 4.13 with a standard deviation of 1.11, indicating considerable variation in user experiences. These variations were strongly influenced by contextual factors such as traffic congestion, weather conditions, and route complexity. The study concludes that evaluating driver performance in app-based transportation services should not rely solely on technical skills, but must also integrate soft skills and situational operational factors. The findings highlight the need for improved training, a more transparent rating system, and algorithmic adjustments to support service quality and driver sustainability.